Reintroduction of freshwater macroinvertebrates: challenges and opportunities. (22nd August 2018) - Jourdan, Jonas; Plath, Martin; Tonkin, Jonathan D.; Ceylan, Maria; Dumeier, Arlena C.; Gellert, Georg; Graf, Wolfram; Hawkins, Charles P.; Kiel, Ellen; Lorenz, Armin W.; Matthaei, Christoph D.; Verdonschot, Piet F. M.; et al.
ABSTRACT: Species reintroductions – the translocation of individuals to areas in which a species has been extirpated with the aim of re‐establishing a self‐sustaining population – have become a widespread practice in conservation biology. Reintroduction projects have tended to focus on terrestrial vertebrates and, to a lesser extent, fishes. Much less effort has been devoted to the reintroduction of invertebrates into restored freshwater habitats. Yet, reintroductions may improve restoration outcomes in regions where impoverished regional species pools limit the self‐recolonisation of restored freshwaters. We review the available literature on macroinvertebrate reintroductions, focusing on identifying the intrinsic and extrinsic factors that determine their success or failure. Our study reveals that freshwater macroinvertebrate reintroductions remain rare, are often published in the grey literature and, of the attempts made, approximately one‐third fail. We identify life‐cycle complexity and remaining stressors as the two factors most likely to affect reintroduction success, illustrating the unique challenges of freshwater macroinvertebrate reintroductions. Consideration of these factors by managers during the planning process and proper documentation – even if a project fails – may increase the likelihood of successful outcomes in future reintroduction attempts of freshwater macroinvertebrates.